Cultivation of Pleurotus sajor-caju on different lignocellulosic substrates and using reeds as an alternative substrate at pilot scale - Karuppuraj, V; Sekarenthiran, S Chandra; Perumal, K (Mushroom Research, 2019)
This research work concentrated on yield improvement of Pleurotus sajor-caju on un explored locally available lignocellulosic substrates such as paddy straw, reeds, sugar cane bagasse and sugar cane leaves. The maximum bioefficiency of P. sajor-caju was obtained from paddy straw (103.36%) followed by reeds (95.17%). From these promising results, pilot scale cultivation was carried out with reeds as an alternative substrate for P. sajor-caju and totally 68.55 kg of fresh fruit bodies were harvested from 95 kg of dry substrate with bioefficiency of 72.15%. Hence, the present findings shows a positive path that, P. sajor-caju can be cultivated on alternative substrates and its efficacy was recorded here at pilot scale.